Tensile and fracture behavior of silica fibers from the Venus flower basket (Euplectella aspergillum). (15th October 2022) - Morankar, Swapnil; Singaravelu, Arun Sundar Sundaram; Niverty, Sridhar; Mistry, Yash; Penick, Clint A.; Bhate, Dhruv; Chawla, Nikhilesh
Highlights: Interweaving lattices formed by spicules on the skeletal wall of Euplectella aspergillum increases the number of free nodes and makes the structure flexible. The varying cross-sectional area of individual spicules have a profound effect on their tensile and fracture behavior. The layered architecture profoundly affects the fracture process by inducing multiple toughening mechanisms. Spicule failure starts from the outer layers and proceeds through these layers to the center core. Abstract: The extraordinary mechanical properties shown by many biological materials stem from their unique hierarchical structures. The spicules of the deep-sea glass sponge, Euplectella aspergillum, show layered architecture and are known to improve toughness in various loading conditions. In the present work, we conducted a systematic study on the tensile and fracture behavior of E. aspergillum's spicules. Tensile tests were performed on three different gage lengths of spicules that compose anchoring structures of E. aspergillum . The cross-sectional area of each spicule was accurately measured using an x-ray microscope. The effect of gage length and varying cross-sectional area on the tensile behavior of spicules is discussed in detail. The interplay between two failure initiation sites, namely, weakest-link flaws and minimum cross-sectional area locations was observed. Weibull statistics were used to quantify the variability in the strengths of spicules as a function of their gage length. The Weibull modulus was observed to decrease with the increase in gage length. The possibility of a bimodal flaw population for a higher gage length of spicules due to the interplay between failure initiation sites is also discussed. The fractography study was utilized to understand the failure and toughening mechanisms of spicules in tensile loading. The fracture toughness of the central core was quantified from fracture surfaces using a linear elastic fracture mechanics model. The present study shows that the failure of spicules initiates in the outer layers and proceeds progressively to the center. The layers surrounding the central core of the spicule resist the crack propagation and increase its toughness.